Healthcare Provider Perspectives on Digital and Interprofessional Medication Management in Chronically Ill Older Adults of Turkish Descent in Germany: A Qualitative Structuring Content Analysis - Rona Bird; Rona Bird; Ilknur Özer-Erdogdu; Ilknur Özer-Erdogdu; Meryem Aslan; Hürrem Tezcan-Güntekin; Hürrem Tezcan-Güntekin (Frontiers Media S.A., 2022)
Medication management for chronically ill older adults with a history of migration can be associated with specific challenges, for instance language barriers. This study examined healthcare provider perspectives on interprofessional cooperation and digital medication management tools as approaches for increasing medication safety for chronically ill older adults of Turkish descent in Germany. Semi-structured interviews were conducted with 11 healthcare providers, including general practitioners, pharmacists, a geriatric consultant, a hospital social worker, and an expert on digitalization in nursing care. The interviews were analyzed by means of qualitative structuring content analysis. This article presents selected results of the analysis relating to medication management, barriers to optimal medication management, interprofessional cooperation, and digital tools. Compliance was perceived to be high among chronically ill older adults of Turkish descent and the involvement of family members in medication management was rated positively by respondents. Barriers to medication management were identified in relation to health literacy and language barriers, systemic problems such as short appointments and generic substitution, and racism on behalf of healthcare providers. Additionally, the respondents highlighted structural barriers to interprofessional communication in the German healthcare system. Furthermore, two technology acceptance models presented in this article to illustrate the respondents' perspectives on a) a digital application for medication management to be used by chronically ill older adults of Turkish descent and b) a digital tool for interprofessional communication. The discussion highlights the implications of the results for medication management within the German healthcare system.